Children with refractory epilepsy demonstrate alterations in myocardial strain. (14th October 2020) - Schreiber, John M.; Frank, Lowell H.; Kroner, Barbara L.; Bumbut, Adrian; Ismail, Moussa O.; Gaillard, William D.
Abstract: Objective: To test whether children with epilepsy have impairments in myocardial mechanics compared to controls without epilepsy. Methods: Children with refractory epilepsy with epilepsy duration of at least 3 years underwent echocardiography including conventional measurements and speckle tracking to assess longitudinal and circumferential strain. Parent‐completed surveys, capturing critical aspects of the children's seizure history and cardiac risk factors, complemented retrospective chart reviews, which also included antiepileptic drug history. Normal echocardiograms from controls, matched for age and gender, were obtained from our institutional database and evaluated for strain. Results: Forty‐one patients (median age = 10 years, interquartile range [IQR] = 5‐15; 58.5% male) were enrolled. Epilepsy etiology included genetic (n = 26), structural (n = 6), genetic and structural (n = 5), infection (n = 3), and unknown (n = 1). No cardiac structural abnormalities were identified. Both longitudinal and circumferential strain were impaired ( P  < .03) in patients compared to controls (median [IQR] = 22.7% [21.2‐24.2] vs 23.6% [22.2‐26.1] and 22.0% [20.3‐25.4] vs 24.5% [22.3‐27.0], respectively), indicating decreased myocardial deformation/contraction. Shortening fraction was higher in patients (37.6% [35.7‐39.7] vs 34.9% [32.5‐38.7], P  = .009); mitral valve E wave inflow velocity (84.8 cm/s [78.4‐92.8] vs 97.2 cm/s [85.9‐105.8], P  = .005) and tissue Doppler lateral E' wave (13.9 cm/s [12.3‐16.1] vs 17.3 cm/s [15.4‐18.5], P  < .001) were decreased compared to controls. Findings were similar in the pairs with epilepsy patients distinguished by the ability to independently ambulate. There was no difference between patients and controls in ejection fraction. Among the epilepsy patients, there were no associations between cardiac measurements and epilepsy characteristics, including seizure type and frequency and cardiotoxic antiseizure medication exposure after correction for multiple comparisons. Significance: Children with refractory epilepsy had impaired systolic ventricular strain compared to controls, not correlated with epilepsy history. Further studies are needed to determine the significance of these changes.